The Effectiveness of Blended Learning in Improving Students Learning Outcomes and Active Participation in Biology Subjects - Mohammad Jamhari; I Nengah Kundera; Syech Zainal; Wa Ode Sitti Mardhiyah (Postgraduate, University of Mataram, 2025)
The rapid development of digital technology in education demands innovative learning models that combine flexibility, interactivity, and collaboration to enhance student engagement and learning outcomes. This classroom action research aimed to analyze the effectiveness of a blended learning model integrated with the cooperative Teams Games Tournament (TGT) approach in improving students’ learning outcomes and active participation in Biology subjects. The study was conducted in two cycles involving 28 students of class XI H at SMAN 4 Palu during the 2024/2025 academic year. Data were collected through observation sheets and cognitive learning tests. The results showed a significant improvement in both teacher performance and student learning outcomes. The average teacher activity increased from 78.2% (Good) to 93.7% (Very Good), while students’ classical mastery rose from 53.57% to 79%, with the N-Gain improving from “Low” (0.29) to “Moderate” (0.49). Statistical analysis using the Wilcoxon Signed-Rank test confirmed a significant difference between pre-test and post-test scores (p < 0.001), with an effect size (r = -1.000) categorized as very large. Additionally, students’ active participation increased from “Fairly Active” to “Active” in most aspects. These findings indicate that integrating blended learning with the TGT model effectively enhances both cognitive achievement and engagement in Biology learning.